Learning from hackers [open-source programming]. - Cioffi, D.F.
The author describes how the open-source movement can teach project managers a lot. Unlike the troublesome computer vandals about whom we read in the mainstream press, open-source hackers are people who ?solve problems and build things?. Most engineers would be proud to be described that way. So would most project managers
Keywords: Open-source hackers; Open-source movement; Open-source programming; Project managers